2016
DOI: 10.1007/s00244-016-0326-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Glutathione S-Transferase Activity and Parental Care Patterns in a Catfish (Pisces, Ariidae) as a Biomarker of Anthropogenic Impact in a Brazilian Harbor

Abstract: Catfish have been used as a model system for studying biochemical mechanisms of biotransformation. The main goal of this study was to identify alterations in hepatic glutathione S-transferase (GST) activity and changes in the parental care pattern of a mouth-brooding catfish, Sciades herzbergii, as a biomarker of anthropogenic impact in a port area on the northeastern coast of Brazil. The fish were sampled from a natural reserve (A1 = reference site) and from an industrialized port area (A2 = impacted site). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The activity of GST is elevated at 24 h under the action of low concentration toxicity (triclosan), significantly inhibited at 72 h, but induced at 168 h in yellow catfish ( Ku et al, 2014 ). In addition, Neta et al have proved that GST activity is changed in different periods in catfish sampled ( Neta et al, 2017 ). Previous study showed that the activities of CBR1 and GST are 2.4 folds and 5.6 folds higher in the 21-month-old rats compared with 6-week-old rats, respectively, but UGT is significantly decreased ( Vyskocilova et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of GST is elevated at 24 h under the action of low concentration toxicity (triclosan), significantly inhibited at 72 h, but induced at 168 h in yellow catfish ( Ku et al, 2014 ). In addition, Neta et al have proved that GST activity is changed in different periods in catfish sampled ( Neta et al, 2017 ). Previous study showed that the activities of CBR1 and GST are 2.4 folds and 5.6 folds higher in the 21-month-old rats compared with 6-week-old rats, respectively, but UGT is significantly decreased ( Vyskocilova et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we considered this area, called A1 in this study, to be an impacted location. Caranguejos Island (2°49"48" S, 44°28"34" W), one of the largest continuous extensions of mangroves in Maranhão and part of the Environmental Protection Area of Baixada Maranhense (Carvalho Neta et al, 2017) is located 30 km from the port area. Caranguejos Island was a low-impact site called A2, in this study.…”
Section: Study Areamentioning
confidence: 99%
“…Biomonitoring, recognized worldwide, uses organisms to assess the quality of aquatic environments and serves as a bioindicator of environmental pollution (Okay et al, 2016). Among the fishing resources found on the coast of Maranhão, Sciades herzbergii (Bloch, 1794), an estuarine catfish, has great commercial relevance in artisanal fishing in the state and has been successfully used in biomarker studies (Carvalho Neta et al, 2017;Soares et al, 2020;Viana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%